Tests computarizados - Prialé Z., R. Fernando (1983)
The impact of microcomputers is discussed as a cultural fact that will bring profound changes in the near future: a society with an ubiquous capacity for treating big amounts of information. The importance of tests for the development of psychology is then analysed. Finaly, the possibility of applying microcomputers to psychometry is discussed trough a concrete example: The BARSIT test.